Effects of Extracorporeal Shock Wave Therapy on Subacromial Impingement Syndrome - Öztürk, Nur Selin (Orthop J Sports Med, 2014)
OBJECTIVES: The purpose of this study was to investigate the effects of extracorporeal shock wave therapy (ESWT) on pain, functional level of the upper extremity, and quality of life (QOL) in patients with subacromial impingement syndrome (SIS). METHODS: This study involved 60 patients with SIS (40 females, 20 males) with a mean age of 52.58 ± 8.05 years. Before the first measurements, all patients were separated into an ESWT group (Group I, n = 30) and a control group (Group II, n = 30) according to a simple random table. Standard physiotherapy and medium-energy ESWT were applied to Group I, and standard physiotherapy and sham ESWT were applied to Group II for 4 weeks. Pain, functional level of the upper extremity and QOL were evaluated before and after treatment. RESULTS: After treatment, the visual analogue scale (VAS) score decreased , and Constant Shoulder Score, Shoulder Pain and Disablity Index (SPADI) and SF-36 score increased statistically in both groups (p < 0.05). Similarly, there were no statistically significant differences in the VAS score, Constant Shoulder Score, and SPADI between Groups I and II after treatment (p > 0.05). CONCLUSION: The results of our study show that applications of medium-energy ESWT at one session a week for 4 weeks had effects similar to those of standard physiotherapy and sham ESWT on shoulder pain, functional level of the upper extremity, and QOL in patients with SIS.